Analisis Nilai Tambah Produk Olahan Ketela Ungu dan Rantai Pasok Ketela Ungu - Hafidh Munawir; Agprasari Ciptaningtyas; Much. Djunaidi; Eko Setiawan (Jurnal Ilmiah Teknik Industri, 2018)
Value added is an indicator of the economic strength of a business. There are several ways to increase added value, namely by processing into new products, preserving, making attractive packaging, and improving the quality of a product. Most of the yield of purple cassava in the Karangnyar area is still sold in the form of raw products and has not been much processed, so the added value is still low. This study identified various processed cassava products, analyzed the added value of processed products, analyzed the added value of purple cassava supply chain and proposed the development of purple cassava. The method used to calculate the added value is the Hayami method. The results of the study showed that there were three alternatives of processed products of purple color namely bakpia, thymus and wingko. The biggest added value of processed products is wingko with an added value of Rp. 26,561 and a ratio of 64%. The highest value supply chain added is UMKM Murakabi network with an added value of Rp. 19,152 and a ratio of 70%, while the network with added value the lowest is a retailer network with an added value of Rp 6,257 and a ratio of 28%. These results indicate that the development of purple cassava business should be done by processing purple cassava in the form of wingko.